THE ETHICS OF CARING FOR INFECTIOUS DISEASE PATIENTS IN ḤANĀ MĪNAH’S NOVEL AL-MAṢĀBĪḤ AL-ZURQ: AKHLAQIYYĀT AL-‘INĀYAH BI-MARDA AL-AMRĀḌ AL-MU‘DIYAH FĪ RIWĀYAH “AL-MAṢĀBĪḤ AL-ZURQ” LI-ḤANNĀ MĪNAH - Teguh Luhuringbudi; Ahmad Thib Raya; Satori Ismail; Tubagus Ade Asnawi (Program Studi Bahasa dan Sastra Arab STIABI Riyadul 'Ulum, 2025)
The novel al-Maṣābīḥal-Zurq presents a case study on tuberculosis as an infectious disease experienced by patients, which requires an ethic of care. This research paper aims to examine how the ethic of care is presented and represented in fictional instincts, narratives, and Arabic rhetoric. This research paper examines the presentation and representation of the ethic of care in the novel al-Maṣābīḥal-Zurq by Ḥanā Mīnah (1954), specifically in relation to tuberculosis as an infectious disease experienced by patients. Textual data such as dialogue and monologue in the novel al-Maṣābīḥal-Zurq are determined through reduction, interpretation, and display techniques by taking into account interdisciplinary styles that include Freud's Psychoanalysis, Gill Branston and Roy Stafford's Narratives, and Rumadani Sagala's Balāghah. The research results indicate that the ethic of care is influenced by poor emotional control, the complex relationship between events and the personalities of fictional characters, and the communication styles employed by novelists. These factors contribute to an increased sustainability orientation in human social interaction. This study contributes to the understanding of how ethics of care are portrayed in Arabic literature dealing with infectious diseases, offering a basis for further comparative literary analysis.